COMPARATIVE FORCE ANALYSIS OF BURNISHING MACHINES BASED ON THE DETERMINATION OF REACTIONS IN THE KINEMATIC JOINTS OF THEIR SPATIAL MECHANISMS - ZALYUBOVSKYI, MARK; ZLOTENKO, BORYS; VOLIANYK, OLEKSII; KRUTII, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Burnishing operations can be performed using various types of equipment; however, the highest efficiency of this process is achieved when machines with work chambers capable of executing complex spatial movements are employed. Depending on the structural design, such machines differ in drive configuration, mechanism kinematics, and technological capabilities, enabling a wide range of operations including grinding, polishing, glazing, surface strengthening, sprue removal, and mixing of heterogeneous components. The structural foundation of these machines typically consists of spatial mechanisms based on rotational kinematic pairs. One of the most important application areas of such machines is the automotive industry, where burnishing is widely used for processing both metal and polymer parts. The process is especially efficient in serial and mass production, where stringent requirements are imposed on surface quality, productivity, and cost-efficiency. Burnishing allows for achieving a high surface finish, removing burrs, rounding edges, improving appearance, and enhancing the operational characteristics of components, which is particularly crucial for automotive assemblies such as transmissions, suspensions, and fasteners. A key condition for the long-term and stable operation of a burnishing machine is the accurate determination of loads in its kinematic pairs. In this study, a three-dimensional CAD model of an eight-link spatial mechanism with dual degrees of mobility was developed, in which the cylindrical chamber follows a complex spatial motion trajectory. Using the “SolidWorks Motion” software package, an analysis was carried out to assess the variation of reaction forces in all rotational joints of the mechanism depending on the geometric parameter δ, which characterizes the center-to-center distance of the chamber. The simulation results revealed the nature of the influence of parameter δ on the peak values of axial and radial reaction forces. It was found that as δ increases up to a certain threshold, a uniform distribution of loads among the kinematic joints is maintained. However, further increase in this parameter leads to localized overloading of specific joints. The obtained results can be applied in the design of burnishing machines for the mechanical engineering and automotive industries to ensure their reliable and energy-efficient operation.